Blood meal acquisition enhances arbovirus replication in mosquitoes through activation of the GABAergic system - Yibin Zhu (Nature Portfolio, 2017)
Transmission of many human viruses depends on replication in their mosquito vectors. Here, Zhu et al. show that glutamic acid digested from the blood meal activates GABA signaling, resulting in suppression of antiviral innate immunity and increased virus replication in mosquitoes.